1 - TIC, pratiques de recherche d’information et production du savoir des enseignants-chercheurs universitaires ivoiriens - Aghi Auguste Bahi, (Africa Media Review, 2007)
Information and Communications Technologies (ICT) challenge academia and sets in place the making of the “knowledge society”. Higher education must face the challenge to stimulate greater competition among university systems. Yet one thing should be underscored in Ivorian universities: there is no automated documention, no library network system; no Ivorian scientific journal has an electronic version or even an e-mail address. The only production of scientific literature remains the “papyrocentrée.” Within such a socio-ethnic framework, what is the place of ICTs in the professional activity of scholars? This question is all the more important today since the dynamism and competitiveness of a university or a research institute, tend to be measured on the basis of its computerization and even its presence on the Internet. This paper presents the primary results of an exploratory study, which focuses on a small sample of actors (scholars, technical and administrative personnel, doctoral students) at Cocody University in Abidjan. With emphasis on individual interviews, the paper assesses their experiences and their logics in view of issues raised by the integration of ICTs and the threat of marginalization of their university space in a globalized scientific environment.